The impact of open search, foreign ownership, and market information on SME exporters’ productivity - Liao, Ching; Colovic, Ana (Management international / International Management / Gestiòn Internacional, 2023)
This article investigates how the export status —incumbent vs. new exporter— affects SMEs’ ability to reap productivity gains. We conduct regression analysis using panel data of Spanish manufacturing SMEs from the PITEC database. Our evidence confirms that the combination of the status of incumbent exporters and of the open search strategy allows SMEs to improve their productivity. This effect is particularly acute when firms are domestically-owned and when they acquire market-oriented information. We contribute to the literature on the relationship between export and productivity by showing that export status matters, and by introducing openness into the discussion.